Pengaruh Kompetensi Guru dan Fasilitas Belajar terhadap Motivasi Belajar Siswa SMA Islam Al-Munir Kota Bekasi - Lely Aisyah Danda Arviana; Natal Indra (Jurnal Riset dan Inovasi Manajemen, 2026)
Students’ learning motivation is a crucial factor in determining the success of the learning process in schools and is influenced by various external factors, including teacher competence and learning facilities. Teachers with adequate competence are able to manage learning activities effectively, while sufficient learning facilities create a conducive environment that supports student engagement and enthusiasm for learning. This study aims to analyze the effect of teacher competence and learning facilities on students’ learning motivation at SMA Islam Al-Munir Bekasi City. This research employed a quantitative method with an associative approach. The research population consisted of all eleventh and twelfth-grade students of SMA Islam Al-Munir Bekasi in the 2024/2025 academic year, totaling 55 students. A saturated sampling technique was applied, in which the entire population was used as the research sample. Data were collected through questionnaires distributed to respondents and supported by interviews, observations, and documentation. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that teacher competence has a positive and significant effect on students’ learning motivation, meaning that higher levels of teacher competence in pedagogical, professional, personal, and social aspects lead to increased student motivation. In addition, learning facilities also have a positive and significant effect on students’ learning motivation, showing that adequate learning infrastructure and facilities are able to enhance students’ interest and enthusiasm for learning. Simultaneously, teacher competence and learning facilities have a significant effect on students’ learning motivation at SMA Islam Al-Munir Bekasi City. The implications of this study emphasize the importance of continuous efforts by schools to improve teacher competence and to provide and maintain adequate learning facilities in order to create a more effective learning process and to strengthen students’ learning motivation.